Understanding the influence of meteorological parameters on biomass of the forest floor of a small pocket of Forest in Central India - Verma, Sangeeta; Jain, Avinash (Indian Forester, 2020)
Seasonal variations in biomass of the forest floor were studied in a small pocket of dry deciduous forest in Central India. Pronounced influence of meteorological parameters was observed on the litter fall in the study area. Total litter collected ranged from 26.6 g/m2 in June to 211.3 g/m2 in February. The peak in the litter fall in the present study was found in the winter and spring seasons (Nov to Mar) coinciding with the drought period in dry deciduous forest types. The ratio of the percentage of the different components of litter- leaf litter, wood litter and herbaceous biomass was also found to be influenced by meteorological parameters.